Subject Priorities of Academic Research in Russia and the World: Analysis of Publication Activity Based on SciVal Data - L. V. Konstantinova; A. M. Petrov; V. V. Vorozhikhin; R. A. Iskandaryan; D. M. Mayakov; D. A. Shtykhno (Вестник Российского экономического университета имени Г. В. Плеханова)
In the situation of global threats and international social and economic pressure on the part of certain countries the development of science becomes very important for Russia and turns into a factor significant both for attaining national goals and effective adaptation to global challenges. In these circumstances the task of making subjects of academic research more acute with due account for national interests and global academic agenda acquires paramount importance. Such methods as qualitative and quantitative analysis, comparison, grouping, ranging and data aggregation were used in the research. The authors on the basis of SciVal data carried out a comparative analysis of subject priorities in academic research in Russian and the world that took into account publication activity indicators, top subject fields and topic clusters, which gave an opportunity to identify specificity of content trends of Russian science in view of global tendencies and find out promising lines of academic research. Sciencemetric tools were widely used for deep and detailed assessment of the most promising trends in academic research.